Automated phototherapy vest - Daud, Siti Asmah (2014)
Phototherapy is the most commonly used therapeutic intervention for the treatment of hyperbilirubinemia (jaundice). Fiberoptic, fluorescent tubes, halogen bulb and also LEDs are among regular light sources used for phototherapy. Phototherapy treatments using florescence light which is usually used in hospitals require continuous uninterrupted treatment period and need infants to be uncovered and only wear eye patches. These conditions are not preferable for infants as they tend to get cold easily and feel uncomfortable. It is also not encouraging for breastfeeding mothers as the treatment needs to be continuous. The rapid development of high intensity light-emitting diodes (LEDs) makes feasible the use of LEDs, among other light sources for use in the design of a garment phototherapy device. The paper describes the design of a phototherapy vest for infants, using ultraviolet (UV) LEDs and Arduino microcontroller for use in reducing bilirubin level in infants with jaundice. The garment phototherapy device is comfortable to wear and infants are no longer required to wear eye patches. The proposed device is portable, uses a small power supply and easy to be operated anywhere.